2016
DOI: 10.1186/s40462-016-0072-y
|View full text |Cite
|
Sign up to set email alerts
|

Metapopulation viability of an endangered shorebird depends on dispersal and human-created habitats: piping plovers (Charadrius melodus) and prairie rivers

Abstract: BackgroundMany species are distributed as metapopulations in dynamic landscapes, where habitats change through space and time. Individuals locate habitat through dispersal, and the relationship between a species and landscape characteristics can have profound effects on population persistence. Despite the importance of connectivity in dynamic environments, few empirical studies have examined temporal variability in dispersal or its effect on metapopulation dynamics. In response to this knowledge gap, we studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
48
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 27 publications
(50 citation statements)
references
References 58 publications
1
48
1
Order By: Relevance
“…AHY true survival was lowest during the flood, which may be attributable to nonbreeding Piping Plovers exhibiting lower survival than breeding Piping Plovers (Catlin et al 2015, Weithman et al in press). With all sandbar habitat on the Gavins Point Reach inundated during the flood (2011), many individuals did not have the opportunity to breed, while others dispersed elsewhere (Catlin et al 2016), leading to the lowest AHY fidelity that we observed. Of those that moved to other breeding locations (the few sandbars that remained above water), many experienced catastrophic nest failure .…”
Section: Discussioncontrasting
confidence: 39%
See 2 more Smart Citations
“…AHY true survival was lowest during the flood, which may be attributable to nonbreeding Piping Plovers exhibiting lower survival than breeding Piping Plovers (Catlin et al 2015, Weithman et al in press). With all sandbar habitat on the Gavins Point Reach inundated during the flood (2011), many individuals did not have the opportunity to breed, while others dispersed elsewhere (Catlin et al 2016), leading to the lowest AHY fidelity that we observed. Of those that moved to other breeding locations (the few sandbars that remained above water), many experienced catastrophic nest failure .…”
Section: Discussioncontrasting
confidence: 39%
“…Moreover, lower densities were related to a higher proportion of double brooding , which may also increase reproductive output. Our results indicated that these fecundity parameters, coupled with increased immigration (Catlin et al 2016), drove the growth of the population following the flood.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…The PLT and LCL subpopulations were predicted to have low extinction probabilities (0.0 and 0.003, respectively), supporting populations totaling 123 and 58 adults, respectively, after 100 yr (Table ; Catlin et al. ). The GVP subpopulation had a greater risk of extinction (0.48) and would likely only support approximately 22 adults by year 100 given the current disturbance regime (Table ; Catlin et al.…”
Section: Methodsmentioning
confidence: 75%
“…We used this baseline model as the foundation for all model scenarios simulated in this study, and field data and parameters that underlie this model can be found in Catlin et al. ().…”
Section: Methodsmentioning
confidence: 99%